Resilience in the process of care in patients with malignant tumor wounds: integrative review (Research, Society and Development, 2020)
Assistance to patients with tumor wounds is a complex task; resilience provides adaptability for handling in different contexts. The objective was to verify the resilience in the process of caring for patients with malignant tumor wounds. This is an integrative literature review carried out in the LILACS, MEDLINE, COCHRANE, CINAHL and SCOPUS (2003-2019) databases with the guiding question: How does resilience occur in the dynamics of care for patients with malignant tumor wounds? Seventeen scientific evidences were identified and three categories of discussion were elaborated: 1) Resilience of the patient with a malignant tumor wound; 2) Resilience of the family member and / or informal caregiver in the process of caring for patients with malignant tumor wounds; 3) Resilience of the multidisciplinary team in the process of caring for patients with malignant tumor wounds. It is concluded that the stigma, the change in body image, the unpredictability and uncontrolled odor and exudate and the constant evidence of having an incurable disease allow the practice of multiple coping strategies by the actors involved in the care, culminating in a better experience. Thus, psychosocial aspects must be considered in the practice of oncology nursing in the care of patients with malignant tumor wounds.